2009
DOI: 10.1111/j.1420-9101.2009.01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic males: a genome‐wide analysis of reproduction and the cost of mating in Drosophila melanogaster females

Abstract: In Drosophila melanogaster, mating radically transforms female physiology and behaviour. Post‐mating responses include an increase in the oviposition rate, a reduction in female receptivity and an activation of the immune system. The fitness consequences of mating are similarly dramatic – females must mate once in order to produce fertile eggs, but additional matings have a clear negative effect. Previously, microarrays have been used to examine gene expression of females differing in their reproductive status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(128 citation statements)
references
References 57 publications
4
121
3
Order By: Relevance
“…Hollis et al [67] examined expression profiles from unmated male and female flies and found a general pattern of feminization of the sex-biased genes in monogamous populations, consistent with predictions from sexual Figure 4 Association with post-mating response and female fitness. (A) Density distribution of significant up-regulated (blue) and down-regulated (red) transcripts in monogamous (versus promiscuous) females along all the tested genes, ranked according to their post-mating reaction (data from a previously published study on the same population; Innocenti and Morrow [44]). (B) Density distribution of the significant transcripts along all the tested genes, ranked by the t-value of their association with female fitness (data from a previously published study on the same population; Innocenti and Morrow [60]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hollis et al [67] examined expression profiles from unmated male and female flies and found a general pattern of feminization of the sex-biased genes in monogamous populations, consistent with predictions from sexual Figure 4 Association with post-mating response and female fitness. (A) Density distribution of significant up-regulated (blue) and down-regulated (red) transcripts in monogamous (versus promiscuous) females along all the tested genes, ranked according to their post-mating reaction (data from a previously published study on the same population; Innocenti and Morrow [44]). (B) Density distribution of the significant transcripts along all the tested genes, ranked by the t-value of their association with female fitness (data from a previously published study on the same population; Innocenti and Morrow [60]).…”
Section: Discussionmentioning
confidence: 99%
“…We compared the expression profile of these transcripts with the female post-mating response characteristic to the ancestral population [44], and found that the expression level of 728 genes is altered in monogamous females to a lesser extent after mating, compared to promiscuous females (hereafter 'virgin-like', see Methods), while the post-mating reaction of the remaining 413 genes is altered to a higher extent in monogamous females compared to promiscuous females (hereafter 'mated-like'), and their proportion is higher than expected by chance (Binomial test: ratio = 0.64, P < 0.0001). In general, genes that are down-regulated in monogamous vs. promiscuous mated females tend to be switched on (up-regulated) by mating (two-tailed MR-GSE test: P < 0.0001, Figure 4A) and genes that are up-regulated in monogamous vs. promiscuous mated females tend to be switched off (downregulated) by mating (two-tailed MR-GSE test: P < 0.0001, Figure 4A).…”
Section: Gene Expression Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known about the responses to mating in males, although they are predicted to primarily involve the replenishment of sperm and seminal fluid storage (Sirot, Buehner, Fiumera, & Wolfner, 2009). Several studies using Drosophila melanogaster have aimed to uncover the gene products that respond to mating, although these studies have examined males and females separately (Dalton et al., 2010; Ellis & Carney, 2010; Innocenti & Morrow, 2009; Lawniczak & Begun, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of female Drosophila have identified male-induced molecular changes associated with a response to sperm and accessory gland proteins, many of which appear to be under antagonistic sexual selection [10,11]. Do changes start to occur during courtship, in anticipation of mating?…”
Section: Introductionmentioning
confidence: 99%